Towards efficient use of noble metals via exsolution exemplified for CO oxidation. Issue 36 (6th September 2019) - Tang, Chenyang; Kousi, Kalliopi; Neagu, Dragos; Portolés, José; Papaioannou, Evangelos I.; Metcalfe, Ian S.
Abstract : Towards controlled nanostructures and efficient use of noble metals via exsolution exemplified for CO oxidation. Abstract : Many catalysts and in particular automotive exhaust catalysts usually consist of noble metal nanoparticles dispersed on metal oxide supports. While highly active, such catalysts are expensive and prone to deactivation by sintering and thus alternative methods for their production are being sought to ensure more efficient use of noble metals. Exsolution has been shown to be an approach to produce confined nanoparticles, which in turn are more stable against agglomeration, and, at the same time strained, displaying enhanced activity. While exsolution has been extensively investigated for relatively high metal loadings, it has yet to be explored for dilute loadings which is expected to be more challenging but more suitable for application of noble metals. Here we explore the substitution of Rh into an A-site deficient perovskite titante aiming to investigate the possibility of exsolving from dilute amounts of noble metal substituted perovskites. We show that this is possible and in spite of certain limitations, they still compete well against conventionally prepared samples with higher apparent surface loading when applied for CO oxidation.